(untitled) (Dialogos, 2017)
Resenha do livro: MOREIRA, Luiz Felipe Viel; QUINTEROS, Marcela Cristina; SILVA, André Luiz Reis. As relações internacionais da América Latina. Petrópolis, RJ: Vozes, 2010.